A multi-step assessment framework for optimization of flood mitigation strategies in transportation networks. (September 2021) - Zhang, Ning; Alipour, Alice
Abstract: Floods can lead to substantial direct damages to transportation infrastructure assets and cause significant indirect losses to communities that rely on the transportation network. This makes it crucial to understand the network's functional and operational deterioration caused by floods to help transportation agencies to either mitigate or plan for consequences of failures. To achieve this goal, this study uses an actual segment of a transportation network as a testbed to develop a network-level multi-step assessment framework to evaluate the flood-related risks and implement specific flood mitigation measures to the testbed. The multi-step framework first accomplishes assessments of the investment of pre-flood mitigation strategies, post-flood asset recovery cost, and indirect post-flood traffic delay and opportunity losses of the network. Then, a life-cycle benefit to cost analysis is applied to estimate the performance of the various flood mitigation strategies. This systematic effort is expected to provide a holistic overview of the flood risk to the network and a conservation-oriented means for optimizing and prioritizing mitigation investments while ensuring that the system resilience is sufficiently improved with respect to capability for absorbing flood hazards and adapting to partially-dysfunctional network operations during floods. Graphical abstract: Image 1 Highlights: Pre-flood mitigation is an effective measure to enhance network resilience and reduce post-flood damages for transportation system. The role of infrastructure network users is highlighted in decision making. Effect of mitigation on direct losses as well as indirect losses is accounted for. Uncertainties associated with flood events are built into a conditional flood mitigation decision-making framework.